Interest in oral and maxillofacial surgery among final year dental students and dental interns and its effect on knowledge and confidence in making clinical decisions - Egbunah UP; Offojebe UL; Adamson OO; Gbotolorun OM (Ibom Medical Journal)
Background: Oral and maxillofacial surgery (OMFS) is a surgical specialty that covers a wide scope of management. This translates to a high inflow of patients and an increased workload for practitioners. This increased workload may affect the interest of young dental practitioners in the specialty which may negatively influence their productivity.